TWITTER MEMES FOR STUDENTS: AN INTERPRETATION AND THEIR PRAGMATICS ROLES - Armita Ayu Sekarsari; Agus Wijayanto (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
The internet has developed and is now widely used, particularly by social media users. Twitter might be considered one of the most well-known social media platforms, despite the fact that there are many other different types. Twitter has grown and expanded to serve people as a source of entertainment in addition to communication. Memes are frequently used by Twitter users to react to social events and to express their feelings. The present study looked into how memes on Twitter are interpreted and used practically. Fifteen data of memes were collected from @PictureFoIder. By using purposive sampling, the memes were purposefully chosen and documentation was used as a data collection method. The chosen memes in the study highlighted students' academic lives. The research revealed that people could express social events or problems ironically and sarcastically through memes. The  finding could be employed as supplementary materials for English teacher to teach pragmatic competence.